RANCANG BANGUN SISTEM IRIGASI CERDAS BERBASIS SENSOR KELEMBABAN TANAH DAN ESP32 UNTUK EFISIENSI AIR PADA TANAMAN PADI - Mus Muallim Nursan; Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT Water use efficiency is a critical factor in rice cultivation, particularly in the context of limited water resources and increasing food demand. Conventional irrigation systems generally rely on fixed schedules without considering actual soil moisture conditions, which can lead to excessive water consumption. This study aims to design and develop a smart irrigation system based on soil moisture sensors and an ESP32 microcontroller to improve water use efficiency in rice cultivation. The developed system utilizes soil moisture sensors to monitor real-time soil water conditions, which are processed by the ESP32 to automatically control a water pump as the irrigation actuator. The research methodology includes hardware design, software development, and system performance testing in an experimental field. The test results indicate that the system can automatically regulate irrigation based on soil moisture levels and reduce water usage compared to conventional irrigation methods. Therefore, the proposed smart irrigation system has the potential to support precision agriculture practices and enhance water use efficiency in rice cultivation.